Molecular typing of the recently expanding subtype B HIV-1 epidemic in Romania: evidence for local spread among MSMs in Bucharest area. - Paraschiv, S; Otelea, D; Batan, I; Baicus, C; Magiorkinis, G; Paraskevis, D (2012)
HIV-1 subtype B is predominant in Europe except in some countries from Eastern Europe which are characterized by a high prevalence of non-B subtypes and circulating recombinant forms (CRFs). Romania is a particular case: the HIV-1 epidemic started with subtype F1 which is still the most prevalent. Previous studies have shown an increasing prevalence of subtype B which is the second most frequent one among the newly diagnosed individuals, followed by subtype C and several CRFs as well as unique recombinant forms (URFs). Our objective was to analyze in detail the characteristics (way of dispersal, association with transmission risk groups) of the subtype B infections in Romania by means of phylogenetic analysis. Among all the individuals sampled during 2003-2010, 71 out of 1127 patients (6.3%) have been identified to be infected with subtype B strains. The most frequent route of infection identified in HIV-1 subtype B patients in Romania was MSM transmission (39.6%), followed by the heterosexual route (35.2%). Many of the patients acquired the infection abroad, mainly in Western European countries. Phylogenetic analysis indicated the existence of a local transmission network (monophyletic clade) including 14 patients, mainly MSM living in the Bucharest area. We estimate the origin of the local transmission network that dates at the beginning of the 90s; the introduction of the F1 and C subtypes occurred earlier. The rest of the sequences were intermixed with reference strains sampled across Europe suggesting that single infection were not followed by subsequent dispersal within the local population. Although HIV-1 subtype B epidemic in Romania is recent, there is evidence for local spread among the MSMs, in addition to multiple introductions.